THE DYNAMICS OF COAL MINING TOWARD SOCIAL ECONOMIC CHANGES IN BAYAH DISTRICT (1999-2015) - Indiyani Indiyani; Rikza Fauzan; Muhammad Ilham Gilang (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2020)
Bayah District is administratively one of the sub-districts in Lebak Regency. Lebak Regency has abundant natural resources, one of which is coal. Coal in Lebak Regency is scattered in various areas, one of which is Bayah District. Coal mining in Bayah District has existed since the Japanese occupation in 1942 1945. Over time, coal mining was reopened in 1999, and coal mining has now become one of the livelihoods in Bayah District. This research is focused on the 1999-2015 timeframe because during that period the dynamics of coal mining occurred which had an impact on the socio-economic life of Bayah District. The method used in this study is a historical method which includes: Heuristics (data collection), Source Criticism, Interpretation, and Historiography. The results showed that the general geographical description of the people of Bayah District were farmers and fishermen. As the community of Bayah Subdistrict realized that there was potential for coal in Bayah District, coal mining in Bayah District began to operate again in 1999. The existence of coal mining resulted in a shift of professions in the Bayah District community.